Feasibility randomised controlled trial to assess the delivery of a novel isometric exercise intervention for people diagnosed with uncomplicated stage 1 hypertension in the National Health Service: key quantitative findings - Melanie Rees-Roberts; Douglas MacInnes; T Pellatt-Higgins; Jamie O’Driscoll; Ellie Santer; Alan West; John Darby; Timothy Doulton; Rachel Borthwick; Katerina Gousia; Vanessa Short; Pauline A Swift; et al. (BMJ Open)
Objectives The aim of this study was to determine the feasibility of delivering personalised isometric exercise (IE) for people with stage 1 hypertension. Is it feasible to deliver an isometric wall squat intervention in the National Health Service and what sample size is required to conduct an appropriately powered effectiveness randomised controlled trial (RCT)?Design Randomised controlled open-label multicentre feasibility study of IE compared with standard care in unmedicated people with stage 1 hypertension.Setting Initially, the study aimed to recruit through primary care, but this process coincided with the advent of the COVID-19 pandemic. Therefore, we shifted focus to direct-to-public advertising and delivery in secondary care.Participants People with unmedicated stage 1 hypertension aged over 18 able to perform IE were included. Patients were excluded if average home systolic blood pressure (sBP) <135 mm Hg; were unable to undertake the study intervention; had a previous history of diabetes mellitus, ischaemic heart disease, moderate-severe valvular heart disease, arrhythmia, stroke or transient ischaemic attack, aortic aneurysm, peripheral arterial disease and uncorrected congenital heart condition; stage 3b chronic kidney disease or worse; heart failure; enrolled in another clinical trial; pregnant or breastfeeding. 41 participants (57±15 years), 59% women, were randomised.Intervention participants were randomised (1:1) to either standard lifestyle advice or an individualised isometric wall squat prescription, performed 4×2-min bouts three times a week for 6 months.Primary and secondary outcome measures We assessed deliverability, attrition, adherence and variance in blood pressure (BP) change.Results IE was found to be easily deliverable to all participants. At 6 months, 34% had withdrawn. Of those who completed IE, 85% of their sessions were at the correct intensity, meeting our retention criterion for success. Variance in BP change was 14.4 mm Hg. The study was not powered to show a difference in BP between groups; however, BP reductions were seen in the intervention group at all study time points compared with baseline. There were no adverse events related to study participation.Conclusions We met our a priori recruitment criteria which allowed us to calculate a sample size (n=542) for a full RCT. The results demonstrate good acceptability and adherence rates to the treatment protocol. Our results show a signal towards a consistent sBP reduction in the IE group compared with baseline.Trial registration number NCT04936022 (https://classic.clinicaltrials.gov/ct2/show/NCT04936022?cond=isometric+exercise&draw=2&rank=7); registry identifier: ISRCTN 13472393.